The Effect of Personal Description Board Game towards Students’ Speaking Skill at SMAN 2 Bangkinang Kota - Helna Safitri; Lusi Marleni; Citra Ayu (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop an English teaching module that is effective and in accordance with the needs of upper secondary level students. The research method used is Research and Development with Plomp model (Preliminary Investigation, Design, Realization/Construction, Test, Evaluation, and Revision, Implementation and Dissemination). At the analysis stage, a survey of student needs and analysis of the applicable curriculum were conducted. The design stage involves the preparation of the module framework and learning materials in accordance with the results of the analysis. Module development is done by designing materials, exercises, and evaluations that are interactive and interesting for students.The developed module is then implemented in the classroom to test its effectiveness. Evaluation was conducted through pre-test and post-test as well as student satisfaction questionnaire on the module. The results showed that the developed teaching module could significantly improve students' reading comprehension and ability. In addition, students showed positive responses to the use of this module, which included increased learning motivation and active involvement in the learning process.Thus, this reading English module can be used as an alternative teaching material that is effective in improving students' English reading comprehension at the upper secondary level. This research is expected to make a positive contribution in the development of teaching materials that are innovative and in accordance with the development of the education curriculum.